2010
DOI: 10.1128/jcm.00654-10
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy and Analytical Sensitivity of IDEIA Norovirus Assay for Routine Screening of Human Norovirus

Abstract: Noroviruses (NoVs) are recognized as the leading cause of epidemic and sporadic acute gastroenteritis. Early detection of NoV is crucial to control the spread of the disease. In this study, we evaluated the diagnostic accuracy, analytical sensitivity, and analytical reactivity of the IDEIA Norovirus assay (an enzyme immunoassay [EIA]) in a prospective and retrospective study design. A total of 557 prospectively collected fecal samples and a panel of 97 archived fecal samples, including 21 different GI and GII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 49 publications
4
44
0
1
Order By: Relevance
“…They found a sensitivity 90.4%, specificity 96.4%, PPV 88.0%, NPV 97.2% and accuracy 95.0%. Costantini et al (6) found that the sensitivity and specificity of the IDEIA Norovirus kit ranged from 57.4% to 77.8% and 79.7% to 91.9%, respectively, when the results were compared by different reference standards.…”
Section: In This Workmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a sensitivity 90.4%, specificity 96.4%, PPV 88.0%, NPV 97.2% and accuracy 95.0%. Costantini et al (6) found that the sensitivity and specificity of the IDEIA Norovirus kit ranged from 57.4% to 77.8% and 79.7% to 91.9%, respectively, when the results were compared by different reference standards.…”
Section: In This Workmentioning
confidence: 99%
“…Norwalk virus was discovered in 1972 by electron microscopy, then cloning and sequencing in 1990 occur. Diagnosis of NoV was done by conventional reverse RT-PCR assay in the mid-1990s followed by real-time RT-PCR (rRT-PCR) assays, which is now the method used for diagnosis of NoV in most clinical laboratories (6).The role of NoV as an important cause of both epidemic and sporadic gastroenteritis were better understood using molecular techniques and sequence analysis (7). Wide differences within this genus were detected using genomic analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the limited laboratory options for propagation of norovirus [55,56] and commercial kits for rapid diagnosis remain underdeveloped [57,58]. As a result, clinical laboratories commonly use reverse transcription-polymerase chain reaction (RT-PCR), immunoassays or hybridization assays [59][60][61][62], which can lead to false positives, provide lower sensitivities and require significant time and materials costs [62][63][64][65][66][67][68][69][70].…”
Section: * Corresponding Authormentioning
confidence: 99%
“…ELISAs can analyze a myriad of pathological samples using multiple screening modes and reporter molecules, giving the assay broad versatility, but their need for high viral loads [5,27,30] limits the assays' application mostly in clinical settings. Despite their relatively lower sensitivity when compared to PCR-based methods [5,20], ELISA-based assays have been used to detect norovirus in human stool samples [5,25,[36][37][38][39][40][41][42][43], human sera [29], and food samples [26,31,32,44,45] Using norovirus GI.1 (Norwalk) virus-like particles (VLPs) as a model viral system, the objective of this study was to develop and evaluate several ELISA-based assays for rapid detection of varying concentrations of GI.1 VLPs (0.037-3.7 μg/mL). HuNoV VLPs are replication-incompetent, macromolecular protein assemblies with capsid structures and antigenic properties resembling those of innate norovirus particles [46][47][48].…”
Section: Introductionmentioning
confidence: 99%